Language in education in sub-Saharan Africa: Language in Africa Special Interest Group (BAAL). (18th June 2015) - Graham, Ross; McGlynn, Caroline; Islei, Annette
<x content-type="archive" xml:space="preserve">Abstract</x> The Language in Africa Special Interest Group (LiASIG) of the British Association for Applied Linguistics (BAAL) is a forum for applied linguistic research in Africa, and invites studies with both a micro and a macro focus. Researchers are concerned with how political, social and educational contexts affect the valuation and use of languages in Africa where multilingualism is the norm. Papers are presented at the SIG annual meeting and in the LiA track at BAAL conferences. The present review covers papers presented between 2012 and 2014 that focus on the interplay of policy and practice, particularly in education.